2021
DOI: 10.1111/jcmm.16803
|View full text |Cite
|
Sign up to set email alerts
|

SLC39A5 dysfunction impairs extracellular matrix synthesis in high myopia pathogenesis

Abstract: High myopia is one of the leading causes of visual impairment worldwide with high heritability. We have previously identified the genetic contribution of SLC39A5 to nonsyndromic high myopia and demonstrated that disease‐related mutations of SLC39A5 dysregulate the TGF‐β pathway. In this study, the mechanisms underlying SLC39A5 involvement in the pathogenesis of high myopia are determined. We observed the morphogenesis and migration abnormalities of the SLC39A5 knockout (KO) human embryonic kidney cells (HEK293… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…TGF-β plays a role in regulating the ECM and acts in many diseases, including myopia [ 38 40 ]. Previous studies have shown that TGF-β is downregulated in the context of scleral tissues with myopia and associated with ECM degradation and fibroblast transformation via the increase in levels of MMP2 or α-SMA [ 41 43 ]. However, bFGF and TGF-β were reported to jointly regulate ocular development in a chick model; TGF-β may be an inhibitor of bFGF, leading to axial elongation and diopter change [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β plays a role in regulating the ECM and acts in many diseases, including myopia [ 38 40 ]. Previous studies have shown that TGF-β is downregulated in the context of scleral tissues with myopia and associated with ECM degradation and fibroblast transformation via the increase in levels of MMP2 or α-SMA [ 41 43 ]. However, bFGF and TGF-β were reported to jointly regulate ocular development in a chick model; TGF-β may be an inhibitor of bFGF, leading to axial elongation and diopter change [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…SLC39 proteins are important transporter proteins for the transport of metal ions from extracellular or intracellular organelles into the cytoplasm [ 14 ]. SLC39A5 , one of the key components of SLC39 protein, also plays an important role in the transport of metal ions such as zinc ions across the cell membrane [ 15 ]. SLC39A5 has been shown to play an important role in Zn + transport within intestinal epithelial cells in vivo, maintaining systemic homeostatic control [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…11 Others have focused on underlying biological mechanisms-the cellular and molecular transduction of visual signals to understand what ultimately drives ocular growth and tissue remodeling. 9 While we continue exploring fundamental mechanisms, clinical interventions are under development and in clinical trials to gauge efficacy. These clinical evaluations include contact lenses that modulate retinal defocus, orthokeratology, and more.…”
mentioning
confidence: 99%
“…More recently, funded work addresses gene and protein expression to understand signals that drive ocular growth. 8,9 Although we are making progress, there is much to do.…”
mentioning
confidence: 99%
See 1 more Smart Citation